A Case Report on Superior Mesenteric Artery Aneurysm: Diagnosis and Treatment with Endovascular Techniques - Nogueira, Oriana; Duque, Mariana; Lopes, Catarina; Silva, Marta; Louro, João; Fernandes, Miguel; Tralhão, José (New Advances in Medicine and Medical Science Vol. 6, 2023)
We present a case of a patient with a superior mesenteric artery, treated successfully with coil embolization. Superior mesenteric artery (SMA) aneurysm is caused by degeneration of the visceral arteries. Although a rarely encountered entity, it requires timely management owing to the high mortality rate associated with rupture, particularly when the aneurysm is saccular in nature. A 30-year-old obese woman admitted to bariatric surgery 15 days before presented to the Emergency Room complaining of abdominal pain for 12 hours. The pain had a sudden onset, with no fluctuation in intensity, located in the epigastrium and right hypocondrium and with no relieving factors. SMAA was diagnosed and the patient underwent successful elective endovascular treatment with coil embolization. Other causes, such as vasculitis or collagen disorders, are left unexplored, since the patient didn’t have any signs or symptoms that required further investigation. Therefore, we believe a congenital cause is most likely, even though we cannot determine that for sure.